Effets Des Conservateurs Acides Et Hydrocolloïdes Alimentaires Sur La Durée De Conservation Du Lait Cru à La Température Ambiante - AGANZE MULUME Dominique; BUCHAGUZI MUZUSANGABO Daniel; MUGISHO ZIRHUMANA Janvier; WEREMUBI MWISHA Sage; KANYERE KAZIGE Orthence; NSAMBU MUKONDUASUMU Pascal; BRIGATTI Thomas; KALUMUNA BARHASHISHWA Jacques (Revue Nature et Technologie, 2024)
The present study was conducted to investigate the effects of acid preservatives (AP) and food hydrocolloids (FH) on the shelf life of raw milk at room temperature (between 20 to 25°C). Raw milk samples were treated with different doses of acid preservatives (citric acid: E330 and ascorbic acid: E300) and food hydrocolloids (food agar-agar: E406 and starch: E1400) to determine the optimal dose that could prolong the shelf life of raw milk while maintaining its physicochemical, microbiological, and organoleptic quality. The results showed that the acid preservatives helped preserve the microbiological quality of the milk samples without significant effects on the final pH values. The food hydrocolloids prevented milk coagulation in the presence of acids only when applied at a dose ≤0.3 g in 100 mL of milk. Citric acid was more effective than ascorbic acid, while food agar-agar (E406) was the best food hydrocolloid. Acid preservatives and food hydrocolloids can be effective tools for prolonging the shelf life of raw milk at room temperature and improving food safety and nutrition in regions where raw milk preservation is a challenge.